The Correlation Between the Variation of Learning Media, Reading Interest, and Students' Understanding of Fiqh Material in Grade VI at SDIT Abuhurairah Mataram - Hamdi, Hamdi; Syarifudin, Syarifudin; Riyan, Lalu; Supardi, Supardi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study aimed to: 1) analyze the correlation between learning media variation and students' understanding of Fiqh material in Grade VI at SDIT Abuhurairah Mataram; 2) examine the correlation between students' reading interest and their understanding of Fiqh material; and 3) determine the joint influence of learning media variation and reading interest on students' understanding of Fiqh material. A quantitative correlational approach was employed, with data collected from 30 students using questionnaires to assess learning media variation and reading interest and tests to measure understanding of Fiqh material. Data were analyzed using Pearson’s correlation coefficient and multiple regression analysis. The results revealed three key findings: 1) a strong positive correlation (r=0.72) between learning media variation and students' understanding of Fiqh material, indicating that diverse teaching tools significantly enhance comprehension; 2) a positive and significant correlation (r=0.65) between reading interest and understanding of Fiqh material, demonstrating that higher reading interest fosters better engagement and comprehension; and 3) a significant joint influence of learning media variation and reading interest, accounting for 68% of the variability in students' understanding (R²=0.68). Regression analysis indicated that learning media variation (b₁=0.45) had a slightly greater impact than reading interest (b₂=0.38). These findings highlight the importance of integrating diverse teaching media, such as visual aids, technology, and interactive activities, alongside fostering reading interest through engaging materials and activities to optimize student comprehension. Practical implications include adopting innovative teaching methods to enhance engagement and learning outcomes.